2014
DOI: 10.1261/rna.041244.113
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry–based relative quantification of proteins in precatalytic and catalytically active spliceosomes by metabolic labeling (SILAC), chemical labeling (iTRAQ), and label-free spectral count

Abstract: The spliceosome undergoes major changes in protein and RNA composition during pre-mRNA splicing. Knowing the proteinsand their respective quantities-at each spliceosomal assembly stage is critical for understanding the molecular mechanisms and regulation of splicing. Here, we applied three independent mass spectrometry (MS)-based approaches for quantification of these proteins: (1) metabolic labeling by SILAC, (2) chemical labeling by iTRAQ, and (3) label-free spectral count for quantification of the protein c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
65
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 44 publications
3
65
0
9
Order By: Relevance
“…Furthermore, the assembly pathway in vitro is characterized by major changes in composition (e.g., only three of the five spliceosomal snRNPs are part of the active C complex [36]). On the other hand, we have previously shown that both the general population of supraspliceosomes and native spliceosomes contained all five spliceosomal snRNPs [15].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the assembly pathway in vitro is characterized by major changes in composition (e.g., only three of the five spliceosomal snRNPs are part of the active C complex [36]). On the other hand, we have previously shown that both the general population of supraspliceosomes and native spliceosomes contained all five spliceosomal snRNPs [15].…”
Section: Resultsmentioning
confidence: 99%
“…phosphorylation, acetylation, ubiquitination) (90). Furthermore, this technique was already successfully used to identify many novel RNA-binding proteins that interact with various classes of RNAs, such as pri- or pre- miRNAs (30), telomeric repeat-containing RNA (91), spliceosomal snRNAs (92,93), viral RNAs (61,76) and expanded GGGGCC hexanucleotide repeats (94). …”
Section: Proteomic Analysis Of Isolated Rbpsmentioning
confidence: 99%
“…Comparisons across different samples were performed after normalization of the total spectra. Spectral counting was used to compare protein abundances at different time points according to a previously described procedure [15,16].…”
Section: Database Searching and Label-free Quantitationmentioning
confidence: 99%